The key role of the most recent EU regulation – the “Digital Operational Resilence Act” in the legal system, contemporary challenges, and Georgian perspectives - Magda Ositashvili (European Scientific Journal, ESJ, 2024)
The challenges of the modern world, such as globalization, digitalization, and other technological advances, have exposed all fields of science, including economics and law, to severe trials. The bold and visionary attempt of legislative bodies in various countries, to evaluate the advantages and disadvantages of existing regulations and consider new ones was complemented by the development of methods and mechanisms to oversee, regulate, and incorporate the latest technological advancements into the legal framework. After ineffective efforts to deal with various objections, the European Union adopted a new regulation called the "Digital Operational Resilience Act." This regulation aims to address the challenges presented by the increasing cybersecurity threats, operational resilience, and digitalization in the financial sector, both ex-ante and ex-post. In this paper, you will learn about the role of “DORA” in the legal system, the economic analysis of the law, the challenges it faces in the European Union, and the perspectives of the Georgian reality. This paper will employ qualitative and theoretical research methods, focusing on the in-depth analysis of existing legal frameworks and expert perspectives. These methods will allow for a comprehensive understanding of DORA's implications in both the European Union and the Georgian context, offering valuable insights into its potential effectiveness and challenges.